2017
DOI: 10.3389/fpubh.2017.00284
|View full text |Cite
|
Sign up to set email alerts
|

Information Quality Challenges of Patient-Generated Data in Clinical Practice

Abstract: A characteristic trend of digital health has been the dramatic increase in patient-generated data being presented to clinicians, which follows from the increased ubiquity of self-tracking practices by individuals, driven, in turn, by the proliferation of self-tracking tools and technologies. Such tools not only make self-tracking easier but also potentially more reliable by automating data collection, curation, and storage. While self-tracking practices themselves have been studied extensively in human–compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…[76][77][78] Recently, West and colleagues 59 described variations in data visualization, data granularity, and units of measure acted as barriers to use as did lack of contextual information. 59 These findings supported our work in that oncologists identified good data visualization as an enabler but made suggestions to include other patient information (granularity) to provide context (i.e., trends over time).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[76][77][78] Recently, West and colleagues 59 described variations in data visualization, data granularity, and units of measure acted as barriers to use as did lack of contextual information. 59 These findings supported our work in that oncologists identified good data visualization as an enabler but made suggestions to include other patient information (granularity) to provide context (i.e., trends over time).…”
Section: Discussionsupporting
confidence: 81%
“…Importantly, the most significant findings of our study centered on appropriate end-users and the importance of engaging others (primary care practitioners, nurses, and patients themselves) as the appropriate end-users. West and colleagues 59 reported primary care physicians and nurses as being more flexible in using tools based on heterogeneous and varied information sources, while secondary care specialists, often expressed the need for standardized information before being able to evaluate it effectively. While oncologists in our study failed to remark on the need for standardization, they did identify other practitioners as appropriate end-users of the CV health tool.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the literature review was to understand how barriers found in prior work may exist across different clinical settings. We adapted our method from our prior work [52]: we searched seven databases (ACM DL, EBSCOHost, Web of Science, SCOPUS, JSTOR, Cochrane, and PubMed) for empirical studies of the use of patient-generated data in clinical settings. The databases were queried using search terms formed from permutations of "patient", "clinician" (and related terms, such as "doctor"), and "self-tracked data" (and related terms, such as "quantified self"), resulting in 1218 results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A final sample of thirteen clinicians (listed in Table 1) were interviewed. While most prior studies of patient-generated data use focus on healthcare within the United States [52], clinicians interviewed in this study all practised within the United Kingdom. The clinical contexts of the participants spanned cardiology, oncology, mental health, surgery, emergency care, general practice, and audiology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 However, thus far most digital self-monitoring devices have unknown reliability and validity, with a lack of evidence for the effectiveness of these technologies. 3,4 So, before digital self-monitoring of MS through smartphones and activity trackers could become common practice, the validity and reliability of these technologies, including their responsiveness to changes in disease status, need to be proved in real-world settings. 5 Another assumption is that smartphone apps and activity trackers could contribute to patient empowerment, with patients taking a more active role in the selfmanagement of chronic diseases, for example through symptom monitoring and adopting lifestyle measures.…”
mentioning
confidence: 99%